THROMBOLYSIS OR PRIMARY PCI FOR MYOCARDIAL INFARCTION WITH ST-SEGMENT ELEVATION? THE STREAM TRIAL (STRATEGIC REPERFUSION EARLY AFTER MYOCARDIAL INFARCTION) - V. A. Sulimov (Столичная издательская компания, 2015)
Ambiguous data about comparability regarding clinical outcomes for prehospital thrombolysis, coupled with timely coronary angiography, and primary percutaneous coronary intervention (PCI) in the early after acute ST-segment elevation myocardial infarction (STEMI), there are now. In the STREAM trial 1892 patients with STEMI diagnosed within 3 hours after onset of symptoms, and whom it was impossible to perform primary PCI within 1 h after the first medical contact, were randomly assigned into two treatment groups: a) primary PCI b) prehospital thrombolytic therapy with bolus tenecteplase (dose decreased by half in patients aged ≥75 years) in combination with clopidogrel and enoxaparin followed by admission to the hospital, where it was possible to perform PCI. Emergency coronary angiography performed if thrombolysis failed. Coronary angiography and PCI of the infarct-related artery were performed in the period from 6 to 24 hours after randomization and thrombolytic therapy in the case of an effective thrombolysis. Primary endpoints include a composite of death, shock, congestive heart failure, or reinfarction up to 30 days. The primary endpoint occurred in 116 of 939 patients (12.4 %) of the thrombolysis group and in 135 of 943 patients (14.3%) of the primary PCI group (relative risk in the group thrombolysis 0.86, 95% confidence interval 0.68-1.09, p=0.21). Emergency angiography was required in 36.3% of patients in the thrombolysis, and the remaining patients, coronary angiography and PCI were performed at a mean of 17 hours after randomization and thrombolytic therapy. Thrombolysis group had more intracranial hemorrhages than primary PCI group (1.0% vs 0.2%, p=0.04; after correction protocol and dose reduction by half of tenecteplase in patients ≥75 years: 0.5% vs. 0.3%, p=0.45). The rate of non- intracranial bleeding in two treatment groups did not differ. Prehospital thrombolysis followed by coronary angiography and timely PCI provide effective reperfusion in patients in the early stages of STEMI that was not possible to carry out primary PCI within 1 h after the first medical contact. Nevertheless, fibrinolysis was associated with a slight increase in the risk of intracranial bleeding.